PhD-supervisors experiences during and after the COVID-19 pandemic: a case study - Krumsvik, Rune J.; Røkenes, Fredrik Mørk; Skaar, Øystein O.; Jones, Lise; Solstad, Stein H.; Salhus, Øystein; Høydal, Kjetil L. (Frontiers in Education, 2024)
COVID-19 has significantly impacted the education sector, and this case study examined nearly three hundred PhD. supervisors in Norway. The study was driven by the urgent need to better understand the professional, social, and existential conditions faced by doctoral supervisors during extended societal shutdowns. This explorative case study builds on our former study among PhD-candidates (Krumsvik et al., 2022) and investigates the experiences of doctoral supervisors when remote work, digital teaching, and digital supervision suddenly replaced physical presence in the workplace, largely between March 12, 2020, and autumn 2022, due to the COVID-19 pandemic. A mixed-methods research approach, incorporating formative dialog research and case study design, was employed to bridge the conceptual and contextual understanding of this phenomenon. The primary data sources were a survey (N = 298, 53,7% women, 46,3% men, response rate 80,54%) and semi-structured interviews (with nine PhD supervisors). Supplementary data collection was based on formative dialog research. It included field dialog (four PhD supervision seminars), open survey responses (1438 responses), one focus group (n = 5), an additional survey (N = 85), and document analysis of PhD policy documents and doctoral supervision seminar evaluations (N = 7). The survey data, interview data, focus group data, and supplemental data focus also retrospectively on the first year of the pandemic and were collected from August 2022 until October 2023. The findings from the explorative case study revealed that the PhD supervisors faced numerous challenges during the pandemic, both professionally and personally. For PhD supervisors who extensively worked from home over a long period, the situation created new conditions that affected their job performance. These altered conditions hindered their research capacity, their ability to follow up with their PhD-candidates, and their capacity to fulfill other job responsibilities. Although the PhD supervisors received some support during the pandemic, it seems that the incremental measures provided were insufficient. The case study results indicate that it is more important than ever to understand the gap between the formulation, transformation, and realization arenas when distinguishing between incremental, semi-structural changes and fundamental changes in PhD. regulations and guidelines brought on by societal crises.